Health informatics a patient-centered approach to diabetes - Hayes, Barbara M., 1955-; Aspray, William (MIT Press, 2010)
In this work, experts in technology, joined by clinicians, use diabetes - a costly, complex, and widespread disease that involves nearly every facet of the health care system - to examine the challenges of using the tools of information technology to improve patient care.
Keywords: Diabetes -- Data processing.; Medical informatics.; elektronické knihy; electronic books